Clinical correlates and profile of patients on antiretroviral therapy: A hospital-based cross-sectional study from a tertiary care institution of North India - Soumya Swaroop Sahoo; Pardeep Khanna; Ramesh Verma; Madhur Verma (Wolters Kluwer Medknow Publications, 2019)
Introduction: HIV/AIDS as a global pandemic has affected each and every region of the world. The HIV epidemic is dynamic in nature with relation to temporal changes, geographic distribution, and modes of transmission. India, though in the declining phase, is still confronting with the varied nature of the spread of the disease. Materials and Methods: This hospital-based cross-sectional study was conducted among four hundred people living with HIV/AIDS (PLHIV) attending the antiretroviral therapy (ART) center of a tertiary care institute of North India. Data were collected from the patients using a predesigned pretested questionnaire maintaining confidentiality. The data were analyzed using simple proportion and percentages. Results: The mean age of the study participants was 32.8 ± 7.4 years. The mean duration of ART intake was 24.5 ± 14.4 months. There was a significant improvement in clinical staging and CD4 count with ART intake among PLHIV. The most prevalent possible route of transmission was found to be heterosexual (85.5%) route. Conclusion: The spread among the population, particularly in the younger age group, reinforces the fact that preventive strategies need to be initiated within the target population at an early stage. Health education and social campaigns are the mainstays for "getting to zero" target.